2010
DOI: 10.1245/s10434-010-1219-5
|View full text |Cite
|
Sign up to set email alerts
|

Tumor Depth as a Predictor of Lymph Node Metastasis of Supraglottic and Hypopharyngeal Cancers

Abstract: Tumor depth is the most useful parameter for predicting lymph node metastases. In clinically node-negative cases, when tumor depth exceeds 1 mm, elective neck dissection must be considered and, when it is less than 0.5 mm, regular clinical follow-up is recommended. Patients with tumor depth between 0.5 and 1 mm should be carefully observed, since they also have a chance of developing nodal metastasis. Venous invasion also indicates high rates of nodal metastasis, therefore elective neck dissection must be cons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
43
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 57 publications
(44 citation statements)
references
References 17 publications
1
43
0
Order By: Relevance
“…Some studies have demonstrated a correlation between invasion distance and lymph node metastasis and have suggested that lymph node metastasis occurs once the tumor has progressed to subepithelial cancer. It is therefore of great significance to obtain a preoperative diagnosis of subepithelial cancer before endoscopic treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Some studies have demonstrated a correlation between invasion distance and lymph node metastasis and have suggested that lymph node metastasis occurs once the tumor has progressed to subepithelial cancer. It is therefore of great significance to obtain a preoperative diagnosis of subepithelial cancer before endoscopic treatment.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, tumor size and tumor depth did not show a correlation 27. In several studies, tumor depth has been shown to be an independent predictor of increased incidence of regional metastasis and worse survival 28–31. The main drawback of these studies is the small number of patients treated.…”
Section: Discussionmentioning
confidence: 99%
“…The results of previous investigations have been inconsistent; there is evidence that tumor thickness correlates with lymph node metastasis . However, results from other studies indicate that the depth of invasion is the only prognostic factor in superficial pharyngeal cancers . Regarding pharyngeal cancers, the current guidelines do not recommend the prediction of prognosis based on either tumor thickness or depth of invasion .…”
Section: Discussionmentioning
confidence: 92%